2016
DOI: 10.1080/21541248.2016.1202634
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cdc42 and Rac1 activities in pheochromocytoma, the adrenal medulla tumor

Abstract: Altered Rho GTPase signaling has been linked to many types of cancer. As many small G proteins, Rho GTPases cycle between an active and inactive state thanks to specific regulators that catalyze exchange of GDP into GTP (Rho-GEF) or hydrolysis of GTP into GDP (Rho-GAP). Recent studies have shown that alteration takes place either at the level of Rho proteins themselves (expression levels, point mutations) or at the level of their regulators, mostly RhoGEFs and RhoGAPs. Most reports describe Rho GTPases gain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…For example, in pheochromocytoma, a NET arising from chromaffin cells of the adrenal medulla, we observed that the activity of Rac1 and Cdc42 was inhibited while their relative expression remained unchanged compared to non-tumor tissue [57]. In this study, we further showed that the inhibition of Rac1 and Cdc42 activities in human pheochromocytomas was directly correlated to reduced expression of the GEFs ARHGEF1 and FARP1, respectively [57,58]. In the very aggressive SDHB-pheochromocytoma, microRNAs controlling the Rho GAP ARHGAP18 expression are specifically overexpressed [59].…”
Section: Control Of Rho Activity In Nets: Important Role Of Rho Gefs supporting
confidence: 54%
“…For example, in pheochromocytoma, a NET arising from chromaffin cells of the adrenal medulla, we observed that the activity of Rac1 and Cdc42 was inhibited while their relative expression remained unchanged compared to non-tumor tissue [57]. In this study, we further showed that the inhibition of Rac1 and Cdc42 activities in human pheochromocytomas was directly correlated to reduced expression of the GEFs ARHGEF1 and FARP1, respectively [57,58]. In the very aggressive SDHB-pheochromocytoma, microRNAs controlling the Rho GAP ARHGAP18 expression are specifically overexpressed [59].…”
Section: Control Of Rho Activity In Nets: Important Role Of Rho Gefs supporting
confidence: 54%
“…Previous studies have demonstrated that increased levels of active myocardial Rac1 renders the heart susceptible to I/R injury [11,24,25]. As other Rho GTPases, Rac1 cycle between an active and inactive state thanks to speci c regulators that catalyze exchange of GDP into GTP (Rac1-GEF) or hydrolysis of GTP into GDP (Rac1-GAP) [26,27]. It has been demonstrated that the activity of Rac1 was regulated by speci c GEF or GAP in different cell settings [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…As other Rho GTPases, Rac1 cycle between an active and inactive state thanks to speci c regulators that catalyze exchange of GDP into GTP (Rac1-GEF) or hydrolysis of GTP into GDP (Rac1-GAP) [26,27]. It has been demonstrated that the activity of Rac1 was regulated by speci c GEF or GAP in different cell settings [26,27]. Thus, it will be worthwhile to investigate which cardiomyocyte-speci c GAP mediates melatonin-induced Rac1 inactivation in our system.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, our study demonstrated that melatonin‐induced Rac1 inactivation contributed to the protective effect of melatonin against OGD/R‐induced injury of H9c2 cardiomyoblasts. Like other Rho GTPases, Rac1 also cycles between an active and inactive state thanks to specific regulators that catalyze exchange of GDP into GTP (Rac1‐GEF) or hydrolysis of GTP into GDP (Rac1‐GAP) (Aslan, 2019; Croise et al, 2017). It has been demonstrated that the activity of Rac1 was regulated by specific GEF or GAP in different cell settings (Aslan, 2019; Croise et al, 2017).…”
Section: Discussionmentioning
confidence: 99%